The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m109.084426
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transporter of SLC22 Family Specifically Transports Prostaglandins and Co-localizes with 15-Hydroxyprostaglandin Dehydrogenase in Renal Proximal Tubules

Abstract: We identified a novel prostaglandin (PG)-specific organic anion transporter (OAT) in the OAT group of the SLC22 family. The transporter designated OAT-PG from mouse kidney exhibited Na ؉ -independent and saturable transport of PGE 2 when expressed in a proximal tubule cell line (S 2 ). Unusual for OAT members, OAT-PG showed narrow substrate selectivity and high affinity for a specific subset of PGs, including PGE 2 , PGF 2␣ , and PGD 2 . Similar to PGE 2 receptor and PGT, a structurally distinct PG transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Their tissue distribution seems consistent with the fact that prostaglandins, which act via paracrine or autocrine regulation, are able to be removed locally to keep the systemic circulating levels low. The recent identification of a renal-specific prostaglandin transporter, OAT-PG in the SLC22 family, suggests how the uptake and elimination may be coordinately handled (Shiraya et al, 2010). Unlike other PG transporters, OAT-PG has narrower substrate specificities with a preference for PGE2, PGF2a, and PGD2.…”
Section: Interaction Of Slc and Abc Transporters With Other Signalingmentioning
confidence: 99%
“…Their tissue distribution seems consistent with the fact that prostaglandins, which act via paracrine or autocrine regulation, are able to be removed locally to keep the systemic circulating levels low. The recent identification of a renal-specific prostaglandin transporter, OAT-PG in the SLC22 family, suggests how the uptake and elimination may be coordinately handled (Shiraya et al, 2010). Unlike other PG transporters, OAT-PG has narrower substrate specificities with a preference for PGE2, PGF2a, and PGD2.…”
Section: Interaction Of Slc and Abc Transporters With Other Signalingmentioning
confidence: 99%
“…Several OAT isoforms appear somewhat specialized for transport of classic signaling molecules and antioxidants and therefore well suited for signaling: liver-expressed OAT2 transports cyclic guanosine monophosphate (107), placentalexpressed OAT4 transports conjugated estrogens (108), olfactory-expressed OAT6 has high selectivity for odorants (109), and OATPG seems specialized for prostaglandins (110). The drug transporters mediating the influx and efflux through tissues and body fluid compartments (e.g., blood, urine, bile, cerebrospinal fluid, and amniotic fluid) could regulate remote communication via transport of key (potentially rate-limiting) metabolites and signaling molecules, hence regulating the movement of these molecules across tissue barriers in the body and also at the cellular level.…”
Section: Remote Sensing and Signaling Hypothesismentioning
confidence: 99%
“…1a). To reveal the underlying mechanism of this increase, we examined the expression of OAT-PG, a recently identified renal transporter involved in the local clearance of PGE 2 in proximal tubules [12,13]. On gestational day 7, the cortical expression of OAT-PG mRNA in rat kidneys was significantly decreased from that of the virgin value (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although these findings suggested an increased level of the renocortical PGE 2 content, later studies revealed unaltered biosynthesis of PGE 2 in pregnant rat kidneys [11]. Recently, we identified a novel PG-specific organic anion transporter (OAT), OAT-PG, exclusively expressed in renal proximal tubules [12]. Later, we further revealed its functional significance in the clearance of renal PGE 2 , demonstrating that renal expression of this transporter primarily determines the renocortical PGE 2 content [13].…”
Section: Introductionmentioning
confidence: 99%